2019
DOI: 10.2147/ijn.s220936
|View full text |Cite
|
Sign up to set email alerts
|

<p>Glucose-Sensitive Nanoparticles Based On Poly(3-Acrylamidophenylboronic Acid-Block-N-Vinylcaprolactam) For Insulin Delivery</p>

Abstract: BackgroundCompared with random copolymers, block copolymerization is easier to prepare for nanoparticles with core-shell structure, and they will have better glucose sensitivity and higher insulin loading.PurposeIn our study, insulin-loaded poly (3-acrylamidophenylboronic acid-block-N-vinyl caprolactam) p(AAPBA-b-NVCL) nanoparticles were successfully prepared and were glucose-sensitive, which could effectively lower the blood sugar levels within 72 hrs.MethodsThe polymer of p(AAPBA-b-NVCL) was produced by reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…It is suggested that the p(AAPBA-b-PTE) NPs can intelligently release insulin in diabetic patients. Compared with our previously prepared p(NVCLco-AAPBA) NPs [13], the addition of PTE did not damage the phenylboronic acid functional group, which had a more stable glucose sensitivity. The results of structural stability test of p(AAPBA-b-PTE) NPs shows that the particle size was relatively stable within 35 days of storage, and there was little difference in particle size.…”
Section: Performance Of P(aapba-b-pte) Npsmentioning
confidence: 67%
See 2 more Smart Citations
“…It is suggested that the p(AAPBA-b-PTE) NPs can intelligently release insulin in diabetic patients. Compared with our previously prepared p(NVCLco-AAPBA) NPs [13], the addition of PTE did not damage the phenylboronic acid functional group, which had a more stable glucose sensitivity. The results of structural stability test of p(AAPBA-b-PTE) NPs shows that the particle size was relatively stable within 35 days of storage, and there was little difference in particle size.…”
Section: Performance Of P(aapba-b-pte) Npsmentioning
confidence: 67%
“…Firstly, acrylic acid-PTE was prepared by using acryloyl chloride to endow the C = C double bond of pterostilbene (scheme 2A), so that it can be used as a part of polymer materials. P(AAPBA) was prepared according to our previously published protocol [13]. Next, as shown in scheme 1C, p(AAPBA-b-PTE) was synthesized via "one-pot" reported in our previous literature [14].…”
Section: Preparation Of P(aapba-b-pte)mentioning
confidence: 99%
See 1 more Smart Citation
“…The first step involved preparing acrylic acid-PTE by using acryloyl chloride to endow the C=C double bond of pterostilbene (Scheme 2 a), so that it could be used as a component in the polymer materials. P(AAPBA) was prepared according to our previously published protocol [ 12 ]. Next, as shown in Scheme 1 C, p(AAPBA-b-PTE) was synthesised via ‘one-pot’, as reported in our previous literature [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Zheng [ 11 ] et al also prepared an amphiphilic glycopolymer (p[LAMA-r-AAPBA]), which can be delivered with lower blood glucose through the nasal cavity. In previous studies, we used N-vinylcaprolactam (NVCL), diethylene glycol dimethacrylate (DEGMA) and 6-O-vinylazeloyl-d-galactose (OVZG) to copolymerise with AAPBA, with which a variety of glucose-sensitive carriers were successfully synthesised [ 12 14 ]. In a summary of previous studies, various formations of polymers, including thermosensitive monomers, pH-sensitive monomers, polyaminoacids, and glycolipid monomers, can be made glucose responsive through various processing methods (Summarised in Additional file 1 : Table S1).…”
Section: Introductionmentioning
confidence: 99%